Electron-impact coherence parameters for electron-impact excitation of laser-excited 174Yb (... 6s6p 3P1) - Hein, Jeff; Kidwai, S.; Zetner, P. W.; Bostock, C.; Fursa, D. V.; Bray, I.; Sharma, Lalita; Srivastava, R.; Stauffer, A. (Journal of physics. B, Atomic, molecular and optical physics, 2011)
We have measured and calculated the P3 collision Stokes parameter for electron-impact collisional de-excitation to the ytterbium (…6s6p 3P1) level from the higher-lying 1P1, 3D1, 2, 3 and 3S1 levels for 20 eV residual energy. These processes are the time-reverse of the experimentally measured processes, where an impact energy of 20 eV was used to collisionally excite the 3P1 target, prepared by resonant laser pumping. Measurements were performed using a crossed-beam apparatus, where excited-state atomic targets were produced using resonant laser radiation incident on the electron-atom interaction region. Calculations were performed in the relativistic convergent close-coupling, convergent close-coupling and relativistic distorted-wave approximations. The theoretical calculations show that the h electron-impact coherence parameter (EICP) is equal to 1/2, independent of the scattering angle. We use this result to present the L⊥ EICP for the (…6s7s 3S1)→(…6s6p 3P1) collision process.
Gesehen am 04.10.2022
Die 174 und 3 im Titel sind hochgestellt, die 1 ist tiefgestellt